Penanggulangan Anak Didik Pemasyarakatan yang Melarikan Diri dari Lembaga Pemasyarakatan Kelas II A Jambi - Nazifah Nazifah; Herma Yanti; Adithiya Nugroho (Wajah Hukum, 2026)
One of the main functions regulated in Law Number 22 of 2022 concerning Corrections is the security function, which aims to prevent correctional students from escaping from correctional institutions. Escapes by correctional students and detainees, both from correctional institutions and state detention centers, are a frequent and recurring problem. Jambi Class IIA Prison is one of the technical implementation units of correctional institutions whose implementation practices also face various challenges. Prisoner escapes are influenced by various factors, including limited security personnel, the physical condition of buildings and security facilities, overcrowding, and psychological factors related to the uncertainty of the legal process. Although the correctional system in Indonesia has been regulated normatively and has undergone regulatory updates, in practice, the strategic role of correctional institutions has not been fully optimal, particularly in terms of prisoner security. This study uses an empirical juridical research type with a socio-legal research approach. Efforts to address the escape of correctional students from the Class II A Jambi Penitentiary are, in practice, predominantly carried out through administrative and preventive approaches, such as increased supervision, enforcement of rules, guidance for correctional students, and recapture of escaped correctional students. Obstacles in addressing escape of correctional students are influenced by structural and institutional factors, including limited number of correctional officers, suboptimal security facilities and infrastructure, and overcrowding.